Placentation in the paca (Agouti paca L) - Bonatelli, M.; Carter, A. M.; Machado, MRF; De Oliveira, M. F.; de Lima, M. C.; Miglino, M. A. (Biomed Central Ltd., 2005)
Background: the paca is a South American rodent with potential as a commercial food animal. We examined paca placenta as part of a wider effort to understand the reproductive biology of this species.Methods: Thirteen specimens between midgestation and term of pregnancy were studied by light and transmission electron microscopy.Results: the placenta is divided into several lobes separated by interlobular trophoblast. Maternal arterial channels and fetal veins are found at the centre of each lobe. In the labyrinth, maternal blood flows through trophoblast-lined lacunae in close proximity to the fetal capillaries. The interhaemal barrier is of the haemomonochorial type with a single layer of syncytiotrophoblast. Caveolae occur in the apical membrane of the syncytiotrophoblast and recesses in the basal membrane, but there is no evidence of transtrophoblastic channels. The interlobular areas consist of cords of syncytiotrophoblast defining maternal blood channels that drain the labyrinth. Yolk sac endoderm covers much of the fetal surface of the placenta. The subplacenta comprises cytotrophoblast and syncytiotrophoblast. There are dilated intercellular spaces between the cytotrophoblasts and lacunae lined by syncytiotrophoblast. In the junctional zone between subplacenta and decidua, there are nests of multinucleated giant cells with vacuolated cytoplasm. The entire placenta rests on a pedicle of maternal tissue. An inverted yolk sac placenta is also present. The presence of small vesicles and tubules in the apical membrane of the yolk sac endoderm and larger vesicles in the supranuclear region suggest that the yolk sac placenta participates in maternal-fetal transfer of protein.Conclusion: the paca placenta closely resembles that of other hystricomorph rodents. The lobulated structure allows for a larger exchange area and the development of precocial young.